2023
DOI: 10.1038/s41418-023-01160-x
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HIF1A-As2 and MYC form a double-positive feedback loop to promote cell proliferation and metastasis in KRAS-driven non-small cell lung cancer

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. KRAS is the main oncogenic driver in lung cancer that can be activated by gene mutation or amplification, but whether long non-coding RNAs (lncRNAs) regulate its activation remains unknown. Through gain and loss of function approaches, we identified that lncRNA HIF1A-As2, a KRAS-induced lncRNA, is required for cell proliferation, epithelial-mesenchymal transition (EMT) and tumor propagation in non-small cell lung cancer (NSCLC) in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…HIF1A-AS2, a KRAS responding lncRNA, was found to be elevated in LC and its high expression was correlated with poor patient prognosis. HIF-1A-AS2 and MYC formed a double-regulatory loop that could pro-mote cell survival, tumor growth and metastasis [ 108 ]. Increased levels of LINC00669 was generally linked with a bad prognosis.…”
Section: Clinical Applications Of Lncrnas and Wnt/β-catenin Signaling...mentioning
confidence: 99%
“…HIF1A-AS2, a KRAS responding lncRNA, was found to be elevated in LC and its high expression was correlated with poor patient prognosis. HIF-1A-AS2 and MYC formed a double-regulatory loop that could pro-mote cell survival, tumor growth and metastasis [ 108 ]. Increased levels of LINC00669 was generally linked with a bad prognosis.…”
Section: Clinical Applications Of Lncrnas and Wnt/β-catenin Signaling...mentioning
confidence: 99%
“…HIF1A-AS2, also known as long intergenic non-protein coding RNA 2055 (LINC02055) or HOX transcript antisense RNA (HOTAIR), resides on chromosome 14q23.2 [ 46 ]. It is transcribed from the antisense strand of the HIF1A gene, encoding the hypoxia-inducible factor 1-alpha (HIF-1α) transcription factor.…”
Section: Lncrnas Inhibit To Biological Processes Of CDmentioning
confidence: 99%
“…Further studies revealed that lncRNA HIF1A-AS2 could directly bind to DHX9 and recruit it to the MYC promoter to activate the transcription of MYC, while MYC was able to respond to the induction of KRAS and promote the expression of lncRNA HIF1A-AS2. LncRNA HIF1A-AS2 regulated and formed a double-feeding loop with MYC in both directions, which further enhanced the proliferation and tumor metastasis of lung cancer cells [ 43 ].
Fig.
…”
Section: Lncrna Regulation At the Transcriptional Levelmentioning
confidence: 99%